The Effect of Linguistic Landscape in Project-Based Learning on Students'Vocabulary Mastery: A Pre-Experimental Study - Widyawati, Ni Kadek Priska Ayu; Padmadewi, Ni Nyoman; Artini, Luh Putu (Tamaddun Life, 2024)
Based on the 21st century there are 6 skills of students that need to be developed such as: Critical thinking, Creativity, Collaboration, Communication, Culture/Citizenship, and Character education/connectivity. To achieve proficiency in a language, it is crucial to develop strong communication skills. For young learners, a good starting point is to focus on memorizing vocabulary, since this will enhance their fluency in speaking. Teaching vocabulary to young learners is challenging, though, as the teacher must utilize an effective teaching method that accommodates the needs of each student. This study focused on the effect of linguistic landscape in project-based learning on students’ vocabulary mastery. This study was conducted at SD Negeri 1 Banjar Jawa, the method used by the researcher was pre-experimental with pre-test and post-test as the instruments to collect the data. The result of this study demonstrated that using the linguistic landscape in project-based learning has a major impact on students' vocabulary mastery. Based on the findings of the pre-and post-tests, students' post-test scores increased significantly after their treatment. Students in class V.B. enthusiastically engaged in the project-based learning process, following its phases and ending in the creation of a linguistic landscape as a final product over the course of six meetings.